Prevalence of criminal legal involvement among emergency department patients: Insights from the National Survey on Drug Use and Health 2021-2023 - Vidya Eswaran; Jun-Hong Chen; Utsha G. Khatri; Phillip L. Marotta; Michael G. Vaughn (PLoS ONE, 2026)
Introduction Criminal legal involvement (CLI) is a known predictor of short- and long-term adverse health outcomes, and those with CLI often use emergency departments (EDs) to access health care. However, the prevalence of CLI among ED patients is unknown. We sought to assess lifetime and past year CLI among those reporting an ED visit for any reason, for substance use and for mental health, and predictors of ED use among those with CLI to inform efforts to establish ED-based screening and interventions. Methods We analyzed data from the 2021–2023 National Survey on Drug Use and Health. Participants reported lifetime CLI, past year CLI and ED visits in the last 12 months for any reason, for substance use and for mental health. We performed descriptive analysis and logistical regression to determine the association between lifetime CLI and ED visits. Results Of those reporting an ED visit for any reason, 19% reported lifetime CLI and 3% reported past year CLI. These numbers rose to 44% (lifetime CLI) and 15% (past year CLI) for substance use related ED visits and 29% (lifetime CLI) and 8% (past year CLI) for mental health related ED visits. Those with lifetime CLI had higher odds of an ED visit for any reason (aOR 1.20, 95% CI 1.12–1.29), for substance use (aOR 1.82, 95% CI 1.36,2.43) and for mental health (aOR 1.54, 95%CI 1.19,1.99). Conclusions EDs should recognize lifetime CLI as social determinant of health which impacts a significant proportion of their patients.